GAMBARAN SPIRITUALITY AT WORK PADA GURU DI JAKARTA - Fatmawati Fatmawati; Maria Dwi Yanika Hesti Nugraha (Universitas Bunda Mulia, 2014)
School is a formal education in which there is the learning process. In this case spirituality at work is needed to improve the quality of the teacher. Spirituality at work is one of the psychological climate in which people who work have an internal life that nourishes and nurtured by meaningful work, and feeling connected with others and with the community in workplace. Purpose of this study is to describe spirituality at work on teachers in Jakarta. The method used is descriptive method, a method in researching the status of a group of people, an object, condition, thought, or an event in the present, the goal is to create a description, picture, or painting in a systematic, factual and accurate information on the facts-facts, properties and relationships between the phenomena investigated. The results obtained in this study is spirituality at work on teachers in Jakarta who are in the low category, with the validity of .30 and reliability of .969. Keywords: Spirituality, spirituality at work, teachers